2015
DOI: 10.1093/schbul/sbv164
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Improves Clinical Symptoms, Quality of Life, Global Functioning, and Depression in Schizophrenia: A Systematic Review and Meta-analysis

Abstract: Physical exercise is a robust add-on treatment for improving clinical symptoms, quality of life, global functioning, and depressive symptoms in patients with schizophrenia. The effect on cognition is not demonstrated, but may be present for yoga.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
209
4
21

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 306 publications
(252 citation statements)
references
References 145 publications
18
209
4
21
Order By: Relevance
“…A systematic review of 39 trials found that engaging in regular physical activity resulted in fewer depressive symptoms, greater aerobic capacity, and improved quality of life among people with mental illnesses including schizophrenia and bipolar disorder (Rosenbaum et al, 2014). Recent meta-analyses have also demonstrated that physical activity contributes to reduction in mental health symptom severity among people with serious mental illness (Dauwan et al, 2015; Firth et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…A systematic review of 39 trials found that engaging in regular physical activity resulted in fewer depressive symptoms, greater aerobic capacity, and improved quality of life among people with mental illnesses including schizophrenia and bipolar disorder (Rosenbaum et al, 2014). Recent meta-analyses have also demonstrated that physical activity contributes to reduction in mental health symptom severity among people with serious mental illness (Dauwan et al, 2015; Firth et al, 2015a). …”
Section: Introductionmentioning
confidence: 99%
“…The MATRICS Consensus Cognitive Battery includes 7 domains that are considered necessary for a complete evaluation of cognitive functioning in schizophrenia [12]. However, most previous studies have only investigated the correlation between physical activity and memory or general cognitive function [13]. …”
Section: Introductionmentioning
confidence: 99%
“…While one recent meta-analysis on humans supports exercise as "a robust add-on treatment" (Dauwan et al, 2015) in schizophrenia, its efficacy is often hard to establish in clinical reality. Indeed, a different meta-analysis of n = 94 schizophrenic patients did not support the hypothesis that physical exercise leads to clinically relevant weight loss in schizophrenia (Krogh et al, 2014).…”
Section: Outlook: Possible New Therapies For Comorbid Obesitymentioning
confidence: 99%